2000
DOI: 10.4141/a00-039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish silage and fish fat on growth performance and meat quality of broiler chicks

Abstract: Kjos, N. P., Herstad, O., Øverland, M. and Skrede, A. 2000. Effects of dietary fish silage and fish fat on growth performance and meat quality of broiler chicks. Can. J. Anim. Sci. 80: 625-632. Two experiments were conducted to study the effect of concentrated fish silage and additional fish fat on growth performance (exp. 1) and meat quality (exp. 2) of broiler chicks. In exp.1, 600 day-old male and female chicks with an initial weight of 36.3 g ± 0.6 SD were allocated to five treatment groups. The treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
3
16
1
7
Order By: Relevance
“…Kjos et al (2000) observed a greater response of fish fat on fatty acid composition in broiler meat than that observed for eggs in the present study when corresponding diets were fed to broiler chicks. Also Krogdahl (1985) has suggested that fatty acid composition of meat changes more readily than that of eggs.…”
Section: Fatty Acid Composition In Egg Yolkcontrasting
confidence: 44%
See 1 more Smart Citation
“…Kjos et al (2000) observed a greater response of fish fat on fatty acid composition in broiler meat than that observed for eggs in the present study when corresponding diets were fed to broiler chicks. Also Krogdahl (1985) has suggested that fatty acid composition of meat changes more readily than that of eggs.…”
Section: Fatty Acid Composition In Egg Yolkcontrasting
confidence: 44%
“…Kjos et al (2000) showed that fish silage could successfully be fed as a part of compound feed for broiler chicks. Limited information exists on the use of fish silage for laying hens.…”
mentioning
confidence: 99%
“…2 Usually, these by-products are discarded as waste that causes serious environmental problems and economic losses (Kjos et al, 2000 andBarroga et al,2001).It is estimated that fish waste production is between 17.9 and 39.5 million tonnes per year, representing an important loss of valuable nutrients. Fish waste can be transformed into fish-meal.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, apresenta a vantagem de não haver a necessidade de neutralização antes da sua utilização no preparo de rações para alimentação animal. Dong et al (1993), Kjos et al (2000); Lien e Ly (2001) Figura 1. pH da silagem ácida de resíduos da indústria de filetagem de tilápias estocadas por diferentes períodos.…”
Section: Resultsunclassified
“…Dong et al (1993), Kjos et al (2000); Lien e Ly (2001) também não relataram a presença de microorganismos em silagem, demonstrando que outras formas podem ser utilizadas com eficiência na prevenção de microorganismos mantendo a qualidade do produto final. Ucci (2003) observou que para se neutralizar silagens com pH abaixo de 3 é necessário quantidades de cal superior a 5%.…”
Section: Resultsunclassified